Processing and Quality Evaluation of Additive Manufacturing Monolayer Specimens. (10th May 2016) - Wendt, Christiane; Fernández-Vidal, Severo Raúl; Gómez-Parra, Álvaro; Batista, Moisés; Marcos, Mariano
Abstract : Although its importance has increased significantly, Additive Manufacturing is not yet a fully accepted industrial manufacturing process for load-carrying parts. The future success of the process group depends on its standardization. This work proposes a methodology for the design, manufacturing, and quality evaluation of specimens manufactured by Fused Layer Modeling that are composed of only one layer (so-called monolayers). The processing methodology and properties of monolayers have not been studied systematically yet. A first systematic design of monolayers for mechanical testing is presented. Rectangular and circular monolayers adapted to the loads of tensile and compression testing are manufactured using different trajectory strategies. Frequently occurring macro- and microgeometrical defects are evaluated and categorized in order to optimize the part quality. This work also studies the effect of some manufacturing parameters such as the gap between print head and machine bed, trajectory strategy, bed leveling, and temperatures on part quality. The most suitable specimens are tested mechanically in tensile or compression tests. In the case of study, tensile strength values are only 8.6% lower than the values for reference tests on the unextruded filament. However, the properties deviate more strongly for compression tests which may be due to the selected specimen geometry.